Investigating surgical site infection after hip fracture surgery - Masters, JPM (2019)
Infection after surgery or surgical site infection (SSI) is a devastating complication for patients and healthcare providers. Hip fracture patients are particularly vulnerable to SSI, and its consequences. Despite its importance, there is uncertainty around the true rate of SSI. This parameter is crucially important to properly power studies that seek to assess interventions that may reduce SSI. One such intervention is the wound dressing. Some dressings including incisional Negative Pressure Wound Therapy (iNPWT) are used in high-risk surgical wounds, and may reduce SSI. There is a need to assess in this context.